Analysis of Problem Solving Ability and Independent Learning Based On IT-Assisted PBL At Nurul Azizi Integrated Islamic Middle School - Siregar, Muhammad Fadhil Hidayat; Hasratuddin, Hasratuddin; Sitompul, Pardomuan (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research is crucial since students struggle with math. They want to "Analysis of Problem Solving Ability and Independent Learning Based on IT-Assisted PBL at Nurul Azizi Integrated Islamic Middle School" . This study is quantitative quasi-experimental. Fix IT issues Scholars value research and freedom. We tested eighth-graders at Nurul Azizi Integrated Islamic Middle School. Random VIII A and B have 30 students. Control and experimental groups are examined. VIIIB/VIIIA comparison. The control group employed conventional methods, while the experimental group used IT-based problem-based learning. Statistics-based research. A statistical analysis. Sample statistics predict a larger population. Parametric statistics estimates population parameters from distribution assumptions. Test a theory before experimenting. 1) Averages define typical. 2) Consistency unites. Three testable hypotheses tell or foretell. Discuss study results: Math issue-based instruction assists SMP IT Nurul 'Azizi pupils. This was expected as the experimental group scored 82.27 and the control 70. SMP IT Nurul 'Azizi's problem-based learning increases student autonomy more than conventional techniques with a 5% significance threshold (5.793>2.002) and a 2-way significant value (t-tailed) of 0.000. Compared to 74, the experimental group scored 85.83. SMP IT Nurul 'Azizi students' arithmetic problem-solving skills are linked to learning, with a 5% significant level (6.55>2.002) and 2-way t-tailed value of This study uses a two-way ANOVA with α = 0.05. At SMP IT Nurul 'Azizi, pupils' arithmetic competency was influenced by their learning model and baseline ability (p-value 0.05). This study uses a two-way ANOVA with α = 0.05. The significance threshold is 0.036, below 0.05.